Concomitant dimorphism in poly[di‐μ‐azido‐(5, 5′‐dimethyl‐2, 2′‐bipyridine)iron(II)]. Issue 8 (21st July 2022) - Setifi, Zouaoui; Bernès, Sylvain; Geiger, David K.; Setifi, Fatima; Reedijk, Jan
Abstract : The crystal structures of two polymorphic forms of a one‐dimensional polymeric Fe II coordination compound are compared, including a computational study for determining which of the two is the most thermodynamically stable. Abstract : The title metal–organic polymer, catena ‐poly[[(5, 5′‐dimethyl‐2, 2′‐bipyridine‐κ 2 N, N ′)iron(II)]‐di‐μ‐azido‐κ 2 N 1 : N 3 ‐[(5, 5′‐dimethyl‐2, 2′‐bipyridine‐κ 2 N, N ′)iron(II)]‐di‐μ‐azido‐κ 2 N 1 : N 1 ], [Fe(N3 )2 (C12 H12 N2 )] n, features alternating μ‐1, 1 ( end‐on mode of coordination) and μ‐1, 3 ( end‐to‐end mode of coordination) double azide bridges, forming chains running in the [100] direction. The octahedral coordination geometry around the Fe II centre is completed by a bidentate 5, 5′‐dimethyl‐2, 2′‐bipyridine ligand. Two polymorphs for this compound were obtained from the crude reaction product, the first in the space group P and the other in P 21 / c . The molecular and crystal structures are very similar for both forms, the main difference being that the eight‐membered Fe(μ‐1, 3‐N3 )2 Fe metallacycle formed with end‐to‐end azide ligands has a nearly flat conformation in the triclinic form and a chair conformation in the monoclinic form. In spite of this geometric difference, both forms have the same density, the same packing index and similar arrangements of the one‐dimensional chains in the crystal. As a consequence, they also share very similar Hirshfeld surfaces and fingerprint plots. However, a density functional theory (DFT) computational study showed that the monoclinic form is more stable than the triclinic form by ca 30.5 kJ mol −1 .